Transient pulse test and morphological analysis of single rock fractures. (January 2017) - Zhao, Yanlin; Zhang, Lianyang; Wang, Weijun; Tang, Jingzhou; Lin, Hang; Wan, Wen
Abstract: Transient pulse tests were performed on single rock fractures at different confining pressures. A new data analysis method based on polynomial fitting was introduced to investigate the relationship between flow velocity and hydraulic gradient. 3D laser scanning was used to quantify the morphological changes of the fracture surface after the transient pulse test or under the hydro-mechanical coupling effect. The results show that the flow velocity versus hydraulic gradient data gradient shows a nonlinear relationship at very low hydraulic, possibly due to strong solid-water interaction, but becomes approximately linear after the hydraulic gradient is high enough. The permeability of a single fracture is sensitive to the confining pressure. As the confining pressure increases, the permeability first remarkably decreases when the confining pressure is lower than a certain value and then decreases at a much lower speed when the confining pressure is higher than that value. Both mechanical and hydraulic apertures decrease at a decreasing rate with the increase in confining pressure. The effect of fracture roughness on the permeability is related to the magnitude of the confining pressure. Rougher fractures have lower permeability at low confining pressures; but the opposite can be true when the confining pressure is high enough. Roughness is no longer critical to permeability when the confining pressure is over a certain value. Highlights: A new method based on polynomial fitting is introduced to analyze the pulse decay data. The permeability first remarkably decreases with higher confining pressure and then at a much slower speed. The effect of fracture roughness on the permeability is related to the confining pressure. The hydro-mechanical coupling reduces the roughness of rock fractures.